Inhibition of the NKCC1/NF-κB Signaling Pathway Decreases Inflammation and Improves Brain Edema and Nerve Cell Apoptosis in an SBI Rat Model - Gong, Yating; Wu, Muyao; Shen, Jinchao; Tang, Jiafeng; Li, Jie; Xu, Jianguo; Dang, Baoqi; Chen, Gang (Frontiers in Molecular Neuroscience, 2021)
Surgical brain injury (SBI) triggers microglia to release numerous inflammatory factors, leading to brain edema and neurological dysfunction. Reducing neuroinflammation and protecting the blood-brain barrier (BBB) are key factors to improve the neurological function and prognosis after SBI. Na+-K+-Cl- cotransporter 1 (NKCC1) and nuclear factor кB (NF-кB) have been implicated in the secretion of inflammatory cytokines by microglia in brain injury. This study aimed to establish the role of NKCC1 in inducing inflammation in SBI, as well as to determine whether NKCC1 controls the release of interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) via phosphorylation of NF-кB in microglia, thus affecting BBB permeability and neuronal cell apoptosis. Male Sprague-Dawley (SD) rats were used to establish an SBI model. This study revealed that compared with the sham group, the expression levels of p-NKCC1, p-p65-NF-кB, and related inflammatory factor proteins in SBI model group significantly increased. After p-NKCC1 was inhibited, p-p65-NF-кB, IL-6, IL-1β, and TNF-α were downregulated, and nerve cell apoptosis and BBB permeability were significantly reduced. These findings suggest that the SBI-induced increase in p-NKCC1 exacerbates neuroinflammation, brain edema, and nerve function injury, which may be mediated by regulating the activity of p65-NF-кB that in turn influences the release of inflammatory factors.